The role of nailfold videocapillaroscopy in Raynaud's phenomenon monitoring and early diagnosis of systemic sclerosis - E. Alessandri; C. Ferrone; G. Zampogna; M. Meroni; C. Pizzorni; M. Cutolo; F. Ravera; A. Sulli (PAGEPress Publications, 2011)
Several connective tissue diseases, in particular systemic sclerosis (SSc), have Raynaud's phenomenon (RP) as their first clinical manifestation. Primary RP represents a benign condition often observed in otherwise healthy subjects, especially women: it is due to an exaggerated response to the physiological cold-induced vasospasm, whereas the secondary form of RP is typically associated with connective tissue diseases, especially SSc. Nailfold videocapillaroscopy (NVC), particulary after the recent technological advances, is a safe and reliable method to observe the microvascular structure and its early changes, especially during the transition from primary to secondary RP. In case of SSc, by considering validated patterns and scoring systems, NVC is the main tool that rheumatologists can rely on, besides the presence of specific auto-antibodies, to perform a very early diagnosis of the disease. This implies the possibility of early treatment of SSc, with an eye of predicting and preventing its major clinical complications.